2007
DOI: 10.1038/sj.ejhg.5201795
|View full text |Cite
|
Sign up to set email alerts
|

De novo t(12;17)(p13.3;q21.3) translocation with a breakpoint near the 5′ end of the HOXB gene cluster in a patient with developmental delay and skeletal malformations

Abstract: A boy with severe mental retardation, funnel chest, bell-shaped thorax, and hexadactyly of both feet was found to have a balanced de novo t(12;17)(p13.3;q21.3) translocation. FISH with BAC clones and longrange PCR products assessed in the human genome sequence localized the breakpoint on chromosome 17q21.3 to a 21-kb segment that lies o30 kb upstream of the HOXB gene cluster and immediately adjacent to the 3 0 end of the TTLL6 gene. The breakpoint on chromosome 12 occurred within telomeric hexamer repeats and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Skeletal changes may progress during growth. Interestingly, translocation breakpoint near HOXB and HOXD with positional effect caused thoracic deformities and digital abnormalities [Spitz et al, 2002; Dlugaszewska et al, 2006; Yue et al, 2007]. We tentatively assume that skeletal anomalies in our patient are associated with haploinsufficiency of the HOXC gene cluster.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Skeletal changes may progress during growth. Interestingly, translocation breakpoint near HOXB and HOXD with positional effect caused thoracic deformities and digital abnormalities [Spitz et al, 2002; Dlugaszewska et al, 2006; Yue et al, 2007]. We tentatively assume that skeletal anomalies in our patient are associated with haploinsufficiency of the HOXC gene cluster.…”
Section: Discussionmentioning
confidence: 59%
“…They suggested that the three rearrangements disturb normal HOXD gene regulation by position effects. Yue et al [2007] reported a boy with severe intellectual disability, funnel chest, bell‐shaped thorax, and hexadactyly of both feet. The patient had a balanced de novo t(12;17)(p13.3;q21.3) translocation.…”
Section: Introductionmentioning
confidence: 99%
“…The coding sequence of tubulin tyrosine ligase-like family member 6 (TTLL6) locates in the chromosomal locus17q21.32. It has been reported the 3' UTR of TTLL6 lies within the distal breakpoint region of De novo t(12;17) (p13.3; q21.3) translocation in a patient with developmental delay and skeletal malformations 17 . However, whether alteration of TTLL6 expression directly caused these syndromes is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, one case with Klippel-Feil anomaly had a translocation involving chromosome band 17q23 (26), which is close to the human hemp orthologous locus at 17q21.3. In addition, several patients with unrelated skeletal abnormalities were shown to bear chromosomal aberrations involving 17q21.3 (28)(29)(30). Therefore, it would be intriguing to investigate whether human hemp expression is affected in patients with Klippel-Feil anomaly and patients with skeletal abnormalities carrying chromosomal aberrations involving 17q21.3.…”
Section: Discussionmentioning
confidence: 99%